Plasmapheresis: A Therapeutic option for Ethylene Di Bromide poisoning (Indian Internet Journal of Forensic Medicine and Toxicology, 2007)
Eleven Ethylene Di Bromide poisoning cases were treated by plasma pheresis. The results are  encouraging. This can be a life-saving therapeutic option.
Keywords: Ethylene; ampoules